Peran Karang Taruna Dalam Meningkatkan Kepedulian Sosial Masyarakat di RT 13 Kelurahan Sukodadi Kecamatan Sukarami - Anggi Santoso; Suryati Suryati; Irpinsyah Irpinsyah (ScidacPlus, 2025)
This research is motivated by the existence of a youth organization operating in the village known as the Karang Taruna organization. Along with the development of the times, there are still young people whose social awareness values ​​are diminishing, their lives have now shifted to living alone, togetherness and mutual assistance have disappeared. This researcher aims to determine the role of Karang Taruna in increasing social awareness of the community in RT 13, Sukarami District, Sukodadi Village. This study uses a descriptive qualitative method with a field research approach involving 4 informants. Data were collected through observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Based on the results of the research conducted, Karang Taruna has a very important role in increasing social awareness of the community in RT 13. In carrying out its role, Karang Taruna carries out social programs that are beneficial to improve community welfare. The programs implemented include; mutual cooperation, Friday blessed basic food packages, deliberations, and August 17th.